2000
DOI: 10.1007/s004670000477
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral vasculitis in Henoch-Schönlein purpura: a case report with sequential magnetic resonance imaging changes and treated with plasmapheresis alone

Abstract: Neurological complications are rare during the course of Henoch-Schönlein purpura (HSP). We report a 7-year-old girl with HSP who presented with seizures, loss of vision and disturbance of consciousness. Magnetic resonance imaging (MRI) showed high signal intensity in the gray and white matter over the left parietal and both occipital lobes, compatible with MRI findings of cerebral vasculitis. The eye fundi revealed multiple branches of retinal artery occlusion. Intravenous pulse methylprednisolone (MTP) follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 9 publications
0
32
0
Order By: Relevance
“…The initial management of patients with suspected cerebral Henoch-Schönlein syndrome includes control of arterial hypertension, seizures and repair of disordered hemostasis. Some trials with plasmapheresis have also been reported (Garzoni et al, 2009;Chen et al, 2000). Anticoagulation agents are advised in patients with secondary anti-phospholipid syndrome (Abend et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The initial management of patients with suspected cerebral Henoch-Schönlein syndrome includes control of arterial hypertension, seizures and repair of disordered hemostasis. Some trials with plasmapheresis have also been reported (Garzoni et al, 2009;Chen et al, 2000). Anticoagulation agents are advised in patients with secondary anti-phospholipid syndrome (Abend et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…According to several case reports, encephalopathy can develop in HSP even without severe hypertension and renal insufficiency, and in these cases CNS vasculitis is suspected as the likely pathogenetic mechanism, although this hypothesis remains unproven by histopathology of the brain [3][4][5][6][7][8]. CNS vasculitis can probably also produce RPLS in HSP on the basis of indirect evidence such as pleocytosis in the cerebrospinal fluid (CSF) and leukocytoclastic vasculitis in skin biopsy [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…In this disease glomerulonephritis frequently occurs as a major complication affecting the prognosis [1], while involvement of the central nervous system (CNS) is uncommon [2]. Encephalopathy associated with HSP has been described in only a small number of case reports [3][4][5][6][7][8][9]. Here, we report a young female patient with HSP nephritis who suddenly showed generalized seizures and cortical blindness with severe hypertension ascribable to renal insufficiency approximately one year after cessation of corticosteroid treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Henoch-Schönlein purpura (HSP) is a small vessel vasculitis that affects predominantly the skin, joints, gastrointestinal tract, and the kidneys (1,2). HSP is seen most frequently in early childhood, although it can occur at any age (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…However, it may be associated with several complications. Neurological symptoms and signs occur in a significant proportion of cases with HSP (2,(6)(7)(8)(9)(10)(11). Although headache and behavioral changes are seen in many patients, severe neurological manifestations such as seizures, intracerebral hematoma, hemiplegia, and encephelopathy are the rare but potentially serious complications (1,2,7,8,10,12,13).…”
Section: Introductionmentioning
confidence: 99%